Integration and visibility of content management, two challenges to achieve at digital broadcasting communication. Case studies about Ser, Cope and Rne - Rodríguez Pallares, Miriam (Revista General de Información y Documentación, 2015)
The content media management has to adapt to the new communication model and advance towards the center of the media organizational chart. Although this is currently being attempted, the different media fail to find enough motivation to exploit all the possibilities of this role, either for economic reasons or for the lack of a strategic perspective. This paper analyses the activity of the content management departments among the three main broadcasting networks in Spain (SER, COPE and RNE), with the aim of identifying practices addressed to a total integration of self-generated content and discover if these departments have the capability to generate their own content under their own signature. The results obtained indicate that all cases studied are different, but all of them manage exclusively media contents and only Cadena SER content management department writes and publishes their own contents.
Keywords: Broadcasting companies; COPE; Documentary visibility; Media companies; Media content management; RNE; SER.